Perspectivas do ensino bilingue: uma análise crítica do parecer CNE/CEB N° 2/2020 e o cenário em Recife-PE. - Viana, Ana Carolina Cordeiro (2023)
Foreign language teaching, especially English, has undergone several transformations over the decades, and currently, its evidence is greater than ever, thanks to the current discourses about a “globalized world” and job opportunities to those who dominate the language. As a result, there is a greater emphasis on its method, which generates discussions about its teach-ing approaches and methodologies, among them, the bilingual approach, which generated the growth of so-called “bilingual” schools which work on the belief that early teaching and In-tensive study of a second language leads to proficiency, better results, and other cognitive advantages compared to other students in a monolingual school. This dissertation aims to ob-serve the adoption of English language teaching from the bilingual approach in schools in Recife/PE, the effects of its lack of regulation and the curricular organization of these educa-tional institutions and to analyze the prospects for the adoption of bilingual teaching in Brazil, observing the pedagogical challenges for its regulation, performing an analysis based on the notes of Critical Discourse Analysis by Fairclough (2003 and 2016) combined with Bhaskar's studies by Barros (2015) regarding Critical Realism. The methodology used will carry out an analysis of the Curriculum Guidelines document for the provision of Plurilingual Education prepared by the National Council of Education and testimonials from parents and guardians available on social networks, to study their effects on society as well as on institutions and perspectives for implementation guidelines.